Innovative electronic worksheets to foster computational thinking in arithmetic sequences and series - Azma, Tiara Rodiana; Hapizah, Hapizah; Darmawijoyo, Darmawijoyo (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: The lack of learning media based on computational thinking (CT) for high school students, especially in the material arithmetic sequences and series, is one of the causes of students' low CT skills.Aim: This research was conducted to develop learning media in the form of electronic student worksheets on the material of arithmetic series and sequences to improve CT skills by utilizing electronic worksheets media.Method: This research employs the R&D method using the Tessmer development model. The research subjects are grade X students from a public high school in Palembang, selected through purposive sampling. The electronic student worksheets were validated by material and media experts and assessed for practicality by teachers and students.Result: The validation value of the developed CT-based Electronic Student Worksheets reached 95.47%, while the practicality assessment of CT-based Electronic Student Worksheets based on the questionnaire obtained a value of 89.97%.Conclusion: Based on the results of the study, it can be concluded that the developed CT-based electronic student worksheets the valid and practical criteria to be used in learning to improve CT skills and understanding of arithmetic sequences and series material for high school students.